Clinical Characteristics of Hospitalized Individuals Dying with COVID-19 in Ulin Regional Hospital Banjarmasin - Haryati Haryati; Mohamad Isa; Ali Assagaf; Ira Nurrasyidah; Erna Kusumawardhani (Faculty of Medicine Universitas Airlangga, 2021)
Background: Corona Virus Disease (COVID-19) has become a global pandemic and has spread to more than 200 countries including Indonesia. South Kalimantan is one of the provinces in Indonesia that has a high COVID-19 mortality rate (case fatality rate 4.1%). Information about characteristic of mortality patients with SARS-CoV-2 infection in Indonesia was limited. The objective of this study to describe clinical characteristics of COVID-19-confirmed deaths at Ulin Regional Hospital Banjarmasin, as a referral hospital in South KalimantanMethods: Medical records of 108 hospitalized patients dying with COVID-19 between March until August 2020 were collected. The recorded information included gender, age, onset and severity of disease, comorbidities, symptoms, signs, and laboratory findingsResults: The 108 confirmed cases of COVID-19 deaths were mostly male (73.1%) aged <65 years old (85.2%). About 84% of the cases had at least one comorbidity or more, like hypertension (44.4%), obesity (38%), and diabetes mellitus (32.4%). Common early symptoms were fever (91.7%) and shortness of breath (89.8%). Laboratory findings included lympocytopenia and eosinophilopenia (80.6% and 72.2%), increased neutrophil lymphocyte ratio (NLR; 86.1%), decreased absolute lymphocyte count (ALC; 72.2%), and hyponatremia (55.6%). Elevated C-reactive protein (CRP; 92.6%), lactate dehydrogenase (LDH; 91.7%), serum glutamic oxaloacetic transaminases (SGOT; 82.4%), and creatinine levels (57.4%). The majority of non survivors were severe-critical stage with severe acute respiratory distress syndrome (ARDS).Conclusion: In this depictive study, patients with comorbidities and severe-critical stage are at risk of death. Laboratory abnormalities were common in non survivors. Shortness of breath may indicate poor prognosis of COVID-19.